2020
DOI: 10.3748/wjg.v26.i29.4327
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and surgical outcomes of sarcomatoid hepatocellular carcinoma

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) is the sixth most common type of cancer and the fourth leading cause of cancer-related death worldwide. Sarcomatoid HCC, which contains poorly differentiated carcinomatous and sarcomatous components, is a rare histological subtype of HCC that differs from conventional HCC. It is highly aggressive and has a poor prognosis. Its clinicopathological characteristics, surgical outcomes and underlying mechanisms of its highly aggressive nature have not been fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…In diffusion weighted imaging (DWI) mapping, multiple cystic changes accompanied by fibrous septum exhibit nonhomogeneous and hyperintense changes in the center, which is also similar to an atypical liver abscess. 15 Drainage in misdiagnosed cases has occurred in clinical practice as previous reports by Wang et al 36 and Shi et al, 37 including two cases in this study (Cases 11 and 12). After investigating 6901 cases of malignant liver tumors, Seo et al 38 reported that PLSC patients had a greater prevalence of rim enhancements than PLC patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In diffusion weighted imaging (DWI) mapping, multiple cystic changes accompanied by fibrous septum exhibit nonhomogeneous and hyperintense changes in the center, which is also similar to an atypical liver abscess. 15 Drainage in misdiagnosed cases has occurred in clinical practice as previous reports by Wang et al 36 and Shi et al, 37 including two cases in this study (Cases 11 and 12). After investigating 6901 cases of malignant liver tumors, Seo et al 38 reported that PLSC patients had a greater prevalence of rim enhancements than PLC patients.…”
Section: Discussionsupporting
confidence: 61%
“…[11][12][13][14] A significantly higher incidence of SHC with hepatitis has been reported, which is similar to the epidemiological characteristics of HCC, indicating the tumorigenesis of SHC. 15,16 Another notable observation has been that PLSC is prevalent in Asian countries, especially in China, the Republic of Korea, and Japan, 17 but there are less cases infected with hepatitis in Japan. A 29-year-old PLSC patient has been reported with a 10-year history of schistosomiasis, who was negative for hepatitis B and C. 9 Besides PLSC, schistosomiasis infection was also reported in bladder sarcomatoid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of HCC still remains poor, and is inextricably linked to its high recurrence and frequent metastases. 4 , 5 Therefore, recent studies on HCC have mainly focused on how to effectively control its rapid growth and prevent its metastasis. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence of sHCC ranges from 1.8% to 3.9% of all HCC cases. 2,3 sHCC can be the primary tumor but is mainly secondary tumors in patients undergoing repeated chemotherapy, transarterial chemoembolization (TACE), radiofrequency ablation (RFA), and percutaneous ethanol injection. 1 sHCC shows a more aggressive phenotype with a higher TNM stage and worse prognosis than classic HCC (cHCC).…”
Section: Introductionmentioning
confidence: 99%